The impact of Industry 4.0 on education contents - Grenčíková, Adriana; Kordoš, Marcel; Navickas, Valentinas (Business: Theory and Practice, 2021)
New jobs will be created because of the Industry 4.0 concept implementation needs, employers will require new, especially digital skills and abilities from their employees. There is a need to change teaching and educational techniques in all types of schools, and instead of being specialized narrowly in one area, education should focus on a much broader overview, as people need to be educated in systemic and interdisciplinary thinking at all types of schools, including nontechnical ones. The main goal of the study is to identify areas on which the content of education should focused on in the future in terms to Industry 4.0. As research methods, a questionnaire survey was conducted in Slovak companies during the period of February – June 2019 along with statistical methods. The survey was carried out by random selection, 350 companies were contacted with a return of 220 responses. The research outcomes declare that changes in workforce qualification structure related to the Industry 4.0 concept implementation should have a positive effect on increasing the competitiveness of companies and increasing production effectivity. Based on the results it is proposed the expected positive changes should be transformed into enforcing the vocational training in companies and structural changes within the Slovak educational system.